The Relationship between Risk Factors and Characteristics of People with Nasopharyngeal Carcinoma - Veranika Ekklesia Andita; Muhammad Noer Shoffi; Ketut Tirka Nandaka; Prajogo Wibowo (GLOBAL HEALTH SCIENCE GROUP, 2026)
Nasopharyngeal carcinoma (KNF) is a malignant cancer that originates from the nasopharyngeal epithelium and is one of the leading causes of cancer death in Indonesia. This disease is related to various environmental and genetic risk factors such as salted fish consumption, smoking habits, exposure to wood burning smoke, alcohol consumption, and genetic factors. Exposure to wood burning smoke contains carcinogenic compounds that can cause chronic irritation and DNA mutations in nasopharyngeal epithelial cells. This study aims to determine the relationship between salted fish consumption patterns, smoking habits, exposure to wood burning smoke, alcohol consumption, and genetic factors with the incidence of nasopharyngeal carcinoma at RSPAL dr. Ramelan Surabaya for the period March 2020 to March 2025. Cross-sectional research was carried out at RSPAL dr. Ramelan Surabaya. A total of 49 consisting of 36 patients with nasopharyngeal carcinoma and 13 non-nasopharyngeal carcinoma patients were selected by total sampling. The dependent variable is nasopharyngeal carcinoma. Independent variables were salted fish consumption patterns, exposure to wood burning smoke, smoking habits, alcohol consumption and genetics. Data was collected using questionnaires that had been tested for validity and reliability, and medical records. The data was analyzed by Chi-square test. There was a significant association between exposure to wood burning smoke and the incidence of nasopharyngeal carcinoma (p = 0.036). Meanwhile, salted fish consumption patterns (p = 0.165), smoking habits (p = 0.586), alcohol consumption (p = 0.288), and genetic factors (p = 0.609) showed no meaningful relationship. This shows that exposure to wood burning smoke is the most influential environmental factor on the incidence of KNF at the research site. There was a significant association between exposure to wood burning smoke and the incidence of nasopharyngeal carcinoma, while salted fish consumption patterns, smoking habits, alcohol consumption, and genetic factors did not show a significant relationship.